Sedimentary and tectonic evolution of the arc zone of Southwestern Ecuador during Late Cretaceous and early Tertiary times - Jaillard, Étienne; Ordoñez, Martha; Berrones, Gerardo; Bengtson, Peter; Bonhomme, Michel; Jimenez, Nelson; Zambrano, Italo (Journal of South American earth sciences, 1996)
The eastern part of the “Celica basin” of southwesternmost Ecuador exhibits Late Cretaceous to Tertiary sediments which belong to the magmatic arc paleogeographic zone. Important N-S to NE-trending faults separate a western, mainly Late Cretaceous series (Río Playas) from an eastern succession (Catamayo-Gonzanamá) of (?) Late Cretaceous to early Tertiary age. The analysis of these sediments indicates a complex geologic history, which recorded the main stages of the early tectonic evolution of the Andes. In the Río Playas area, a submarine andesitic volcanic pile (Celica Fm) represents the products of a volcanic arc of probably Albian age. It is apparently overlain by a thick, early Late Cretaceous series of volcanic flows and coarse-grained volcaniclastic high-density turbiditic beds (Alamor Fm), the deposition of which might result from the Mochica phase (late Albian-early Cenomanian) Deformation, uplift and erosion (early Peruvian phase) are followed by the sedimentation of unconformable marls and greywackes of marine open shelf to deltaic environment. These comprise Santonian and/or Campanian fine- to mediumgrained deposits (Naranjo Fm), abruptly overlain (late Peruvian phase ?) by fan-delta coarse-grained marine deposits of latest Cretaceous age (Casanga Fm) They are locally capped by undated, partly volcaniclastic red beds, indicating an important regression/uplift of latest Cretaceous-early Tertiary age. In the Catamayo-Gonzanamá area, thick subaerial andesitic volcanic rocks (Sacapalca Fm) are intruded by Paleocene to early Eocene plutons and are overlain by undated fluvial red beds. They express uplift movements of latest Cretaceous-early Tertiary age. To the South, these are capped by slumped lacustrine black shales and greywackes of possible Maastrichtian-Paleocene age (Gonzanamá Fm) Farther north, the Sacapalca volcanics and red beds are overlain by variegated shales, sandstones and conglomerates, dated as latest Oligocene-early Miocene (Catamayo Fm) They are eroded by an angular unconformity and capped by early Miocene volcanics and sediments, which express an early Miocene deformation phase. The apparent sedimentary hiatus including most of Eocene-Oligocene times is interpreted as a result of the late Paleocene and late Eocene Incaic tectonic phases. - Resumen - La parte oriental de la “Cuenca Celica” del Suroeste ecuatoriano presenta sedimentos del Cretáceo superior al Terciario, que pertenecen a la zona paleogeográfica del arco magmático andino. Importantes fallas de dirección N-S separan una serie occidental, mayormente del Cretáceo superior (Río Playas), de una serie oriental (Catamayo-Gonzanamá) de edad Cretaceo superior (?) y Terciario inferior. El análisis de estos depósitos evidencia una historia geológica compleja, que registró las etapas principales de la evolución tectónica precoz de los Andes. En la zona de Río Playas, volcánicos andesíticos submarinos (Fm Celica) representan los productos de un arco magmático de probable edad albiana. Parecen ser sobreyacidos por una serie potente de coladas volcánicas y turbiditas volcano-clásticas de alta densidad (Fm Alamor) Su deposición podría ser relacionada con la fase tectónica Mochica del Albiano superior-Cenomaniano inferior. Estas rocas fueron levantadas y erosionadas (fase Peruana temprana) antes del depósito discordante de margas de plataforma marina y grauacas deltaicas. Estas comprenden depósitos de grano fino de edad Santoniano y/o Campaniano (Fm Naranjo), abruptamente sobreyacidos (fase Peruana tardía ?) por conglomerados marinos de cono aluvial costero (fandelta) del Cretáceo terminal (Fm Casanga) La serie se termina localmente con capas rojas no datadas, en parte volcanoclásticas, que indican una regresión y/o un levantamiento de edad Cretáceo terminal o Terciario inferior. En la zona de Catamayo-Gonzanamá, una espesa serie de rocas volcánicas andesiticas subaéreas (Fm Sacapalca) está intruida por plutones del Paleoceno a Eoceno inferior, y sobreyacida por capas rojas fluviátiles no datadas, que expresan un levantamiento importante en el Cretáceo superior-Terciario inferior. Hacia el Sur, están sobreyacidas por lutitas negras y grauacas lacustres de posible edad maastrichtiana-paleocena, con deformaciones sinsedimenatrias (Fm Gonzanamá) Hacia el Norte, los volcánicos y capas rojas Sacapalca están sobreyacidos por lutitas, areniscas y conglomerados abigarrados, datados del Oligoceno terminal a Mioceno inferior (Fm Catamayo) Estos están erosionados por volcánicos y sedimentos del Mioceno inferior, lo que indica una deformacián de edad Mioceno inferior. El hiato aparente de gran parte del Eoceno-Oligoceno está interpretado como una consecuencia de las fases tectónicas incáicas del Paleoceno superior y Eoceno superior.
Elektronische Reproduktion der Druck-Ausgabe 25. Februar 1999
Gesehen am 07.12.2022